2009
DOI: 10.1007/s11151-009-9211-6
|View full text |Cite
|
Sign up to set email alerts
|

Merger Simulation in the Presence of Large Choice Sets and Consumer Stockpiling: The Case of the Bottled Juice Industry

Abstract: Bottled juice, Brand competition, Consumer stockpiling, Differentiated products, Distance metrics, Merger analysis, L13, L41, L66, C81,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Numerous papers analyzed the role of contextual variables and showed that price fluctuations have an effect on consumer propensity to stockpile products for future consumption (e.g. Pofahl, 2009;Hendel and Nevo, 2003). They buy more when there is a price reduction and time their purchases to exploit price fluctuations (Meyer and Assunção, 1990;Mela et al 1998).…”
Section: Consumer Stockpiling According To Price Fluctuations and Typ...mentioning
confidence: 99%
“…Numerous papers analyzed the role of contextual variables and showed that price fluctuations have an effect on consumer propensity to stockpile products for future consumption (e.g. Pofahl, 2009;Hendel and Nevo, 2003). They buy more when there is a price reduction and time their purchases to exploit price fluctuations (Meyer and Assunção, 1990;Mela et al 1998).…”
Section: Consumer Stockpiling According To Price Fluctuations and Typ...mentioning
confidence: 99%